PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN PROMOSI TERHADAP PROSES KEPUTUSAN PEMBELIAN E-COMMERCE TOKOPEDIA DI KOTA SEMARANG - Sari, Dila Purnama; Soliha, Euis (Proceeding SENDI_U, 2021)
This study aims to discuss and analyze the effect of product quality, price perception and promotion on the Tokopedia e-commerce purchasing decision process in Semarang City. The population in this study are consumers who have bought goods or products in Tokopedia, Semarang City. The research method used was purposive sampling. The sample used was taken as many as 100 respondents with the data collection method using a questionnaire.The results of the study prove that product quality is positive for the purchasing decision process.price perception has no effect on the purchasing decision process and promotion has a positive effect on the purchasing decision process.